2016
DOI: 10.5812/ircmj.36676
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a Hospital-Based Educational Program Based on the Health Belief Model on Self-Care Behaviors of Heart Failure Patients

Abstract: Background: The empowerment of heart failure (HF) patients to improve self-care behaviors through appropriate training programs is necessary. Evidence has indicated a lack of theory-based trials in hospitals and healthcare centers, both of which represent important health promotion settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
4
0
1
Order By: Relevance
“…The third outcome variable in this study is the rate of readmissions of heart failure patients after teach-back education. Kaveh et al [ 55 ] report that, during hospitalization, the patient's concern about recurrence of heart disease increases his/her adherence to self-care behaviors, but with the improvement of clinical conditions, it is predicted that recurrence and readmission will occur due to reduced adherence to treatment regimens [ 55 ]. Regarding readmission, the present study shows that teach-back education reduces the frequency of readmission of HF patients to the hospital.…”
Section: Discussionmentioning
confidence: 99%
“…The third outcome variable in this study is the rate of readmissions of heart failure patients after teach-back education. Kaveh et al [ 55 ] report that, during hospitalization, the patient's concern about recurrence of heart disease increases his/her adherence to self-care behaviors, but with the improvement of clinical conditions, it is predicted that recurrence and readmission will occur due to reduced adherence to treatment regimens [ 55 ]. Regarding readmission, the present study shows that teach-back education reduces the frequency of readmission of HF patients to the hospital.…”
Section: Discussionmentioning
confidence: 99%
“…The participants with heart failure (HF),[ 26 27 28 29 30 31 32 33 ] coronary heart disease (CHD),[ 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 ] hypertension (HTN),[ 13 39 40 41 42 43 44 ] coronary artery bypass graft (CABG),[ 20 45 46 47 48 ] myocardial infarctions (MI),[ 17 19 49 50 51 ] patients with pacemaker,[ 52 ] heart valve disease,[ 53 ] and cardiac rehabilitation[ 18 ] were highest and lowest target groups in studied papers, respectively. The detailed characteristics of included studies are revealed in [ Table 2 ].…”
Section: Resultsmentioning
confidence: 99%
“…In general, study results revealed that theory-based interventions were effective in all types of outcomes among studies target groups. [ 13 14 15 20 26 27 28 29 30 31 32 33 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 ] Improving awareness and information in chronic conditions as CVDs results in achieving practical outcomes such as follow-up, adherence to self-care and self-management behaviors, promoting QoL, and healthy lifestyle. A targeted multimedia educational intervention can be effective in reducing the adverse effects of chronic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…48-50 For example, patients with HF assigned to an educational intervention reported significant improvements in HBM elements of self-care. 51,52 No changes were observed in controls. However, explicit information that describes how theory was used in the design of interventions and that links intervention techniques to theory is often lacking, 45 despite the availability of frameworks that can be implemented to assist in this process.…”
Section: Change Agents In Self-care Interventionsmentioning
confidence: 91%